Determination of the relevant market as a criterion of assessment of concentration effects in the practice of antitrust authorities - Kostecka-Jurczyk, Daria (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
Determining the relevant market is the first and the most important step in antimonopoly proceedings due to the fact that the market position of an enterprise is always determined from the relevant market perspective. In respect of mergers, establishing the relevant market is essential in analysing whether the aim of the concentration is to distort and limit competition on the market. The author of the article focuses on describing methods for determining the relevant market applied by antimonopoly authorities.
Keywords: postępowanie antymonopolowe; konkurencja; rynek właściwy